The relationship between mindfulness and depression: examining the chain mediating role of shyness and core self-evaluation - Lin Liu; Hailing Jia; Baiyang Qiu; Anbang Zhang; Qian Zhang (BMC Psychology)
Abstract Background There is evidence to suggest that individuals with the personality trait of shyness are more prone to depression, and a possible key factor in the process of shyness leading to depression is core self-evaluation. Given the prevalence and cross-cultural nature of shyness in humans, it is crucial to understand the factors that reduce shyness, enhance core self-evaluation, and ultimately lower depression. This study aims to examine whether mindfulness affects depression through sequential pathways involving shyness and core self-evaluation. Method We adopted a two-phase sampling method, recruiting an initial sample of 646 college students (Sample 1). We conducted a questionnaire survey using the Chinese version of the Five Factor Mindfulness Scale, the revised Cheek and Buss Shyness Scale, the Core Self-Evaluation Scale, and the Chinese version of the Beck Depression Inventory-II. We constructed a chain mediation model to examine the relationship between mindfulness and depressive symptoms, with shyness and core self-evaluation as mediating variables. Subsequently, based on Sample 1, we purposively selected a subsample of 269 college students with higher shyness scores (Sample 2) and re-examined the chain mediation effect. Results Higher levels of mindfulness were associated with lower levels of depressive symptoms, and this relation was mediated through shyness and core self-evaluation. Conclusions These results highlight that mindfulness can influence depression through the sequential pathway of shyness and core self-evaluation, and the importance of considering mindfulness practices in psychological interventions to help college students, especially shy college students, to reduce their shyness levels, improve core self-evaluation levels, and ultimately prevent and/or treat their depressive symptoms.